Analysis of dye degradation products and assessment of the dye purity in dye‐sensitized solar cells. (29th October 2015) - Rendon, Sabine M. K.; Mavrynsky, Denys; Meierjohann, Axel; Tiihonen, Armi; Miettunen, Kati; Asghar, Imran; Halme, Janne; Kronberg, Leif; Leino, Reko
Abstract : Rationale: For commercialization of dye‐sensitized solar cells (DSSCs), improvement of their long‐term stability and efficiency is important. A key component in solar cells is the dye, its high purity and high stability. Here, methods for dye extraction and purification, and for determination of dye purity and dye degradation in DSSCs, were developed. Methods: A method was developed for extraction of the dyeZ907 from intact solar cells using a water/ethanol mixture containing tetrabutylammonium hydroxide. TheN719 dye synthesized in our laboratory was purified by gel filtration on Sephadex LH20. These dyes, along with the dyesN3 and RuL2 (NC)2, were analyzed using nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography coupled to an electrospray ionization quadrupole‐time‐of‐flight mass analyzer (LC/MS) operating in negative ionization mode. Results: Purification of the synthesizedN719 removed several impurities, including its undesired isomer with the thiocyanate ligand attached to ruthenium through sulfur instead of nitrogen. The dyesN719 andZ907 were successfully extracted from solar cells and together withN3 and RuL2 (NC)2 analyzed by LC/MS, althoughN719 isomerized almost immediately in basic aqueous solution. The [M–H] −1 ions were observed and the measured mass was within a ±6 ppm range from the exact mass. Conclusions: LC/MS in combination with NMR spectroscopy was shown to provide useful information on dye structure, purity, and on the efficiency of the purification methods. These methods allow for further studies of solar cell dyes, which may provide the detailed information needed for the improvement and eventual commercialization of the solar cell technology. Copyright © 2015 John Wiley & Sons, Ltd.